Mechanical Characterization of Steel for Fastening in a Wide Range of Strain Rate - CADONI, E.; BRAGOV, A. M.; DOTTA, M.; FORNI, D.; KONSTANTINOV, A.; LOMUNOV, A.; RIPAMONTI, A. (Engineering Transactions, 2011)
In this paper, the preliminary results of the mechanical characterization in a wide range of strain rate of the 30MnB4 steel, usually adopted for fasteners, are described. In this study the different issues required to implement the dynamic test results in numerical code have been analyzed. Different experimental techniques have been used for different strain rates: univer- sal machine, Hydro-Pneumatic Machine, JRC-Modified Hopkinson Bar and Split Hopkinson Pressure Bar. The failure at high strain rate has been examined by means of fast digital image recording systems. The material shows enhanced mechanical properties increasing the strain rate: this fact can be taken into consideration to improve the product design and the manu- facturing process. The experimental research has been developed in the DynaMat laboratory of the University of Applied Sciences of Southern Switzerland and in the Laboratory of Dy- namic Investigation of Materials in Nizhny Novgorod, in the frame of the Swiss – Russian Joint Research Program.